Evaluation in the time of crisis: evidencing value at a centre for teaching and learning during the Covid-19 pandemic. Issue 2 (3rd April 2022) - Marin, L. F.; Valgardson, B. A.; Watson, E.
ABSTRACT: As is the case with many Centres for Teaching and Learning, prior to the global health crisis in 2020 our Centre primarily obtained feedback to inform its programming based on participation and satisfaction. As a result of the crisis, we could not rely on previous sources of information and needed to implement new strategies for evidencing the value that our Centre was providing. In this article we describe how our Centre adapted our services and resources due to the demands of the Covid-19 pandemic and the ways in which we modified our feedback processes to evidence the value of the services we provided.